The contribution of new US technologies to US differential diagnosis of nonpalpable lesions - Rizzatto, Giorgio (Radiology and oncology (Ljubljana), 2004)
Background. Gray-scale ultrasound (US) patterns are still the best indicators of the risk of malignancy and correlation with mammography and guidance to bioptical procedures are still the gold standard in breast diagnosis. But recent technological advancements in ultrasound offer new diagnostic capabilities that integrate conventional US imaging: 3D, CAD, perfusion imaging and elastography. Conclusions. The US technologies allow to differentiate and grade the vascularity of breast lesions (both with conventional technologies and with contrast enhancers) and to evaluate the elastic properties of the normal and pathologic tissues (elastography). Both these technologies are on the way of becoming commer cially available on medium and high-end US instruments. But they must still be considered as research tools because their diagnostic efficacy requires more widely clinicaltesting.
Keywords: Breast Neoplasms; Contrast Media; Diagnosis; Dojka, novotvorbe; dojke; Kontrastna sredstva; Limfatična metastaza; Lymphatic Metastasis; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Mammography; Mamografija; rak (medicina); Ultrasonography; ultrazvočna diagnostika